Tools to improve discharge equity: Protocol for the pilot TIDE trial - Kirsten Austad; Cecilia Thai; Alegna Zavatti; Nhi Nguyen; Diana Bautista-Hurtado; Patrick Kenney; Noelia Lugo; Joo H. Lee; Howard Lanney; Ziming Xuan; Erika G. Cordova-Ramos; Mari-Lynn Drainoni; et al. (Contemporary Clinical Trials Communications)
Background: Written discharge instructions after hospitalization promote patient understanding and positive clinical outcomes. Despite the rising prevalence of patients with non-English language preference (NELP) in the U.S., most hospitals do not routinely provide discharge instructions in their preferred language, thereby placing them at higher risk for medical errors and hospital readmission. Innovative solutions to close this implementation gap at hospital discharge for patients with NELP are needed. The Tools to Improve Discharge Equity (TIDE) intervention leverages communication practices proven effective in addressing communication barriers to create language concordant discharge tools from hospital discharge paperwork. Methods: We present the protocol for a type I hybrid implementation-effectiveness pilot randomized trial. The TIDE intervention includes a translated medication calendar, pictographs, and an audio recording of the discharge instructions in the patient's preferred language. We will recruit an estimated 50 patient participants from the hospital's top four non-English language groups—Spanish, Haitian Creole, Cape Verdean Creole, and Vietnamese—as well as the nurse and in-person interpreter caring for them. Outcomes include patient recall of primary diagnosis and overall understanding of discharge instructions using a newly developed 24-point score, patient experience, implementation measures (acceptability, feasibility, and appropriateness), and clinical effectiveness (including hospital reutilization). A mixed methods evaluation will identify determinants of intervention uptake to guide selection of multi-level implementation strategies to test in a future hybrid type III trial. Discussion: The TIDE intervention is the first hospital discharge intervention designed for patients with NELP. Result will inform future efforts to improve the safety and equity of the hospital discharge process. Trial registration: clinicaltrials.gov NCT05988229 (August 14, 2023) https://classic.clinicaltrials.gov/ct2/show/NCT05988229.